ANALISIS KOSTUM KARAKTER TOKOH UTAMA PADA FILM SERIES KOREA “SWEET HOME” - Kusuma, Paku; Sintowoko, Dyah Ayu Wiwid (Narada : Jurnal Desain dan Seni, 2024)
One of the supporting pillars of creative industries is fashion. Fashion has great potential value to improve the economy. Promotion of fashion, especially through film platforms, has proven to be successful in our fashion industry. Costume references from the film industry also become a reference for fashion designer in developing their works. The increasing dominance of film series from Korea since 2002 has significant impact on the development of this industry. This research aims to find out how the costumes in the Korean film series 'Sweet Home' are constructed to depict the three dimensions of the main characters, namely: Cha Hyun Soo, Pyeon Sang Wook, and Seo Yi Kyeong. Qualitative descriptive methods are used with mise-en-scene as an analytical approach. Data was obtained through observations and literature study. The results of the analysis show that the four costume elements, namely: upper clothing, body, legs, and accessories are closely related to the three dimensions of character, namely physiological, sociological, and psychological for each character which are connected to the perception of acceptance by the audience. This relationship places a strong emphasis on trends according to the time setting of the film's background depiction, so that the successful acceptance of the adaptation of the webtoon comic into a film is very visually satisfying for viewers. These three characters, who belong to different generations, are able to neatly represent the expectations of the audience with costumes that have been adapted to each character's personality so that they often become a reference for post-pandemic dressing patterns.